Pengaruh Penambahan Larutan Daun Salam Terhadap Sifat Organoleptik ikan Kembung - Rizki Mustofa; Ari kristiningsih; Murni Handayani; Mardiyana Mardiyana; khoeruddin wittriansyah (Universitas Djuanda, 2025)
This study aimed to determine the effect of adding bay leaf solution on the pH and organoleptic quality of mackerel during room temperature storage. The experiment used a Completely Randomized Design (CRD) with four concentrations of bay leaf solution (0%, 15%, 20%, and 25%) and two observation times (0 and 24 hours), each with three replications. The bay leaf solution was prepared through washing, grinding, boiling, filtering, and dilution. The observed parameters included pH, eye, gill, mucus, flesh, aroma, and texture based on organoleptic evaluation. The results showed that at 0 hours, treatments with 20% and 25% concentrations produced significantly higher pH values compared to other treatments (p<0.05), while after 24 hours no significant differences were found (p>0.05). Organoleptic tests indicated a decline in quality for all parameters after 24 hours of storage. Significant effects of bay leaf solution were observed only in certain parameters during the initial storage stage, particularly gills and texture, while its effectiveness decreased during longer storage. In conclusion, bay leaf solution has the potential to maintain the quality of mackerel during the early stage of room temperature storage but is less effective in preventing quality deterioration after 24 hours.